Measurements of self‐efficacy in musculoskeletal rehabilitation: A systematic review. (20th September 2018) - Picha, Kelsey J.; Jochimsen, Kate N.; Heebner, Nicholas R.; Abt, John P.; Usher, Ellen L.; Capilouto, Gilson; Uhl, Tim L.
Abstract: Objectives: Low self‐efficacy is a barrier to rehabilitation adherence. Before an intervention can be implemented to improve self‐efficacy, assessment is required. It is currently unknown if a standard measure of self‐efficacy has been used to assess this in patients with musculoskeletal conditions, specifically for home exercise programmes (HEPs). The aim of the present study was to determine which self‐efficacy scales are being used in conjunction with exercise adherence, identify if any scale has been developed to evaluate self‐efficacy for HEPs and evaluate their psychometric properties. Methods: Data sources included CINAHL, MEDLINE, Pubmed, PsycInfo, and Sport Discus. Studies had to include patients suffering from a musculoskeletal injury, pain or disorder; a measure of rehabilitation adherence; and patient's self‐efficacy. The study population, self‐efficacy measurement used, study quality as identified with the Modified Downs and Black checklist, results pertaining to self‐efficacy, and level of evidence were extracted. The Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines were followed and 29 articles were included. Results: A total of 14 scales assessing self‐efficacy were identified but no scale to assess self‐efficacy for HEPs was found. Many scales report internal consistency but lack test–retest reliability and validity. Conclusions: The scales identified were specific to condition or tasks, and not applicable for all musculoskeletal patient populations. It is important, both for use in the clinic and for research, that outcome measures used are reliable and valid. Unfortunately, no scale was found to assess self‐efficacy for HEPs, which is problematic as self‐efficacy is task specific. As HEPs are essential to rehabilitation, there should be a scale designed specifically to assess self‐efficacy for this task.